ECONOMIC OF UTILISATION OF CLIMATE SMART AGRICULTURAL PRACTICES AMONG RICE FARMERS IN DASS LOCAL GOVERNMENT AREA, BAUCHI STATE, NIGERIA - Ibrahim. N.; Bose, A. A.; Hamidu, B. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study analysed the economic utilisation of Climate Smart Agricultural Practices (CSA) among rice farmers in Dass Local Government Area of Bauchi State, Nigeria. A multi-stage sampling technique was used to select 120 rice farmers randomly. Primary data were collected using structured questionnaires and analysed using descriptive statistics, net farm Income, and a logit regression model. The results revealed that rice farming was male-dominated (62.5%), with moderate access to extension (54.2%) and credit services (77.5%). The results revealed that majority (66.7%) of the farmers utilised CSA practices. Early maturing varieties (57.5%), zero tillage (52.5%), and good market strategies (51.7%) were the most utilized CSA practices. The total cost, gross income and net farm income were ₦532,954.76, ₦862,755.75 and ₦329,800.99 per hectare, respectively. The results on factors influencing utilisation of CSA practices, revealed that education was positive and highly significant (P<0.01). Similarly, marital status, occupation, access to extension services and years of farming experience were significant at P<0.05. The constraints affecting the farmers were inadequate capital (4.1), high cost of inputs ( 3.8) and inadequate enlightenment ( 3.7) on CSA practices, among others. The study recommended that financial institutions should promote farmer-friendly credit facilities. Also, provision of subsidised inputs to the rice farmers in order to promote utilisation of CSA practices on rice production in the study area.